Selective extraction of silver from the semiconductor wastes - Seng, T. B.; Mat, Hanapi; Othman, Norasikin (1998)
With the current emphasis on industrialization and the wide spread information technologies, electronics becomes the worlds largest and the most rapidly expanding industry. These activities are not only lead to provide a better life but also create wastes that harmful to the environment and human life. Therefore, the productions of wastes which containing hazardous chemicals such as metals and cyanide ions have to go treatment before discharging to an environment. However on seeking to comply the environmental legislation, several treatment techniques have been used by the industries. For instance, chloride oxidation is among the popular methods of cyanide reduction. Accumulations of metal hydroxide sludge also contribute to another environmental problem. For instance, the annual manufacturing capacity of PC board created at least estimated annual revenue of US 0.50 billion can generate up to 100,000 metric tone of sludge which containing high metals content such as silver. In semiconductor industries silver is mainly used as electric contacts and conductors. Currently, there are technologies that can be used to extract silver from the semiconductor wastes such as floatation, ion-exchange, smelting and refinery, biosorption, liquid membrane and liquid-liquid extraction. Therefore, the development of cheap and simple technology to treat the sludge while recovering the precious metals such as silver is required to help the industries to solve their environmental problems. Liquid-liquid extraction technology, which commonly used in hydrometallurgy is simple and easy to scale up could provide a good alternative compare to other techniques for this sort of application. In this paper we will present the preliminary results of the selective extraction of silver from semiconductor wastes which involving the characterization of the sludge, leaching process and finally selective liquid-liquid extraction of silver from leached solution carried out using appropriate extractants.